Fenomen polityzacji buddyzmu w XXI wieku: Buddyzm jako narzędzie budowania ideowej tożsamości narodu w Birmie (Mjanma) i na Sri Lance oraz realizowania polityki zagranicznej w kontekście współzawodnictwa indyjsko-chińskiego w Azji = The Phenomenon of Politicisation of Buddhism in the 21st Century - Kłodkowski, Piotr (Studia religiologica, 2017)
The text focuses on the issues of political interpretation of Buddhism in Myanmar and Sri Lanka, as well as on its role as an element of diplomatic soft power in bilateral Indo-Chinese relation-ship. The author analyses the problems of self-immolation, non-violence vs violence policies and national identity building in the context of re-defining Buddhism in the political realities of se-lected Asian countries.